(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the semantic subtleties of diminutive forms belonging to the family of nouns, the morphosemantic aspects of these forms, their manifestations in speech styles, as well as the negative and positive aspects expressed through the speaker’s goal. The expression of such meanings was confirmed by fragments of artistic, journalistic and colloquial style.